2018
DOI: 10.3390/jsan7030040
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimisation of a Solar Energy Harvesting System for Wireless Sensor Network Nodes

Abstract: The Wireless Sensor Networks (WSN) are the basic building blocks of today’s modern internet of Things (IoT) infrastructure in smart buildings, smart parking, and smart cities. The WSN nodes suffer from a major design constraint in that their battery energy is limited and can only work for a few days depending upon the duty cycle of operation. The main contribution of this research article is to propose an efficient solar energy harvesting solution to the limited battery energy problem of WSN nodes by utilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…Some studies have shown that modelling algorithms can be refined to optimise this technique in practice. This has allowed for the creation of MPPT systems with very low energy consumption, which maximise the active time of photovoltaic cells [29], and also systems that are heavily optimised for IoT applications [30].…”
Section: Sources Of Energymentioning
confidence: 99%
“…Some studies have shown that modelling algorithms can be refined to optimise this technique in practice. This has allowed for the creation of MPPT systems with very low energy consumption, which maximise the active time of photovoltaic cells [29], and also systems that are heavily optimised for IoT applications [30].…”
Section: Sources Of Energymentioning
confidence: 99%
“…The articles that appear in this Special Issue form a diverse collection of topics studied under the scope of WSANs for smart cities. These include low-cost IoT implementation for smart-village settings [1], smart parking systems exploiting WSNs [2], Machine-To-Machine (M2M) Networking over LTE for smart-city services [3], WSN-driven smart waste-management systems for sustainable cities [4], user-support systems with wearable sensors and cameras [5], a SmartInsoles Cyber-Physical System (CPS) for mobile gait analysis [6], energy-harvesting systems for WSNs [7], and IoT for WSNs in smart cities [8].…”
Section: Summary Of Contributionsmentioning
confidence: 99%
“…The ubiquity of smart-city services can only be ensured with the significantly increased lifetime of sensors and WSNs. The authors of Reference [7] propose an efficient solar-energy-harvesting system with pulse-width modulation (PWM) and maximum power-point tracking (MPPT) to sustain the batteries of WSN nodes. Following the design of several models for a solar-energy harvester system, the authors run a series of simulations for solar powered DC-DC converters with PWM and MPPT to obtain optimum results.…”
Section: Summary Of Contributionsmentioning
confidence: 99%
“…In contrast, low-level models are highly implementation-dependent and hence tightly associated with specific architectures. Low-level modeling relies on equivalent circuits of the integrated components, which are then combined into a system model to accurately describe the behavior of a given hardware architecture [ 26 , 27 , 28 ]. These low-level models can be implemented via specialized simulation software environments, like SPICE [ 29 ] or Simulink (a visual programming tool for model-based design that supports automatic code generation in Matlab), or directly executed by using EH-WSN-oriented simulation tools, like GreenCastalia [ 30 ], SolarCastalia [ 31 ], SensEH [ 32 ] and others, which already include an energy module that integrates the energy-harvesting, rechargeable battery and energy consumption models.…”
Section: Solar Energy-harvesting Modelsmentioning
confidence: 99%